By design: Professional learning ecologies to develop primary school teachers' makerspaces pedagogical capabilities. (8th March 2019) - Stevenson, Michael; Bower, Matt; Falloon, Garry; Forbes, Anne; Hatzigianni, Maria
Abstract: Makerspaces embody a growing movement of educators promoting constructionist learning with physical materials and digital technologies such as 3D design and 3D printing. As it gains traction in K‐12 settings, the maker movement represents an interesting context in which to explore how professional ecologies can equip teachers with the knowledge, skills and dispositions needed to implement twenty‐first century learning in their school context. This study investigated the roles of different participants from industry, school leadership and colleagues in influencing teachers' confidence, enthusiasm, capabilities and beliefs when teaching in makerspaces. Utilising triangulated observations of activities through online questionnaires at beginning, middle and end points, as well as postproject interviews, the study explored the participation of 27 primary school teachers in a blended professional learning programme, followed by classroom delivery of modules focusing on tablet‐based 3D design applications and the use of newly instaled 3D printers. Reporting no prior knowledge or experience with makerspaces, quantitative analyses revealed significant increases in teachers' confidence and enthusiasm. Qualitative analyses of questionnaire and interview data underscored the influence of hands‐on and theoretically grounded professional learning providing practical exposure to constructionist ideas, design thinking methodologies and 3D design technologies. Findings reveal the importance of targeted professional learning coupled with a substantial collegially supported implementation phase, as well as support from school leaders and industry partners to promote meaningful pedagogical change in technology‐mediated maker‐based learning.